Antibiotic Susceptibility Pattern of Bacteria Isolated from an Urban Referral Hospital in Dhaka City (Bangladesh Journal of Medical Microbiology, 2016)
The present study was to assess the pattern of antibiotic susceptibility of the isolated bacteria in an urban referral hospital in Dhaka City. A total of 393 bacterial strains were isolated from various specimens over a l0-months period. The majority of the organisms were Escherichia coli Q3.33oh) followed by Klebsiella species (27.480 ), Staphylococcas aureus (l7.Oioh),Lcinetobacter species (8.l4yo), Pseudomonas species (7.l2Yo), and others. The thirdgeneration Cephalosporins Hke Ceftriaxone, Ceftazidime and Cefotaxime were sensitive against 45-66yo isolated Enterobacteriaceae. The first- and second-generation Cephalosporins were less effective. The sensitivity to Ciprofloxacin of various Enterobacteriaceae was only between 33-4Oo compared to 52.8-67.9Vo against Gentamicin. Majority of the Enterobacteriaceae were resistant to Ampicillin, whereas almost all of the Enterobacteriaceae (94-100%o) were sensitive to Imipenem. Ahont97.UY;s Acinetobacter species were susceptible to Imipenem. Sensitivity of the organism (Acinetobacter) to third-generation Cephalosporins ranged between 50-560 , whereas 40.60/o were found sensitive to Ciprofloxacin. The sensitivity to Chloramphenicol, Co-trimoxazole, Cephalexin and Ampicillin ranged between 9.3oh to 34.30 . About 93.0%o of Pseudomonas species were sensitive to Imipenem. The rate of susceptibility to Gentamicin and Netilmicin was higher than those of the Ciprofloxacin and Ceftriaxone (67.80/o and, 53.57o vs, 39.2yo), About 707o of isolated S. aureus were resistant to OxacilHn but all were sensitive to Vancomycin. The result of this study would help the physicians to make a judicious choice of,.anti.biotics for therapeutic purposes.Bangladesh J Med Microbiol 2008; O2 (02):7-ll